Hubungan Penggunaan Aplikasi Online Food Delivery dengan Indeks Massa Tubuh (IMT) pada Anggota Polri di Korlantas Polri Tahun 2025: The Relationship Between the Use of Online Food Delivery Applications and Body Mass Index (BMI) among Police Officers in the Traffic Corps of the Indonesian National Police in 2025 - Putri Apriliani Ayuningtyas; Arif Hidayatullah; Agus Purnama (Journal of Nursing Education and Practice, 2025)
Introduction: The rapid development of digital technology has significantly transformed consumption patterns, including within institutions such as the Indonesian National Police. Online Food Delivery (OFD) applications provide convenience in accessing food but may also influence users’ nutritional status, particularly by increasing Body Mass Index (BMI). Objective: This study aimed to examine the relationship between the use of Online Food Delivery applications and Body Mass Index (BMI) among members of the Indonesian National Police at the Traffic Corps (Korlantas) in 2025. Methods: This quantitative study employed a descriptive-analytic approach with a cross-sectional design. The study population consisted of 902 police officers at Korlantas POLRI, with 90 respondents selected using probability sampling through simple random sampling. Data were collected using a validated and reliable questionnaire on OFD application use, as well as direct anthropometric measurements (weight and height) to calculate BMI. Data were analyzed using univariate and bivariate methods to assess the association between OFD application use and BMI. Result: The findings revealed that more than half of the respondents (53.3%) were active users of OFD applications, and a considerable proportion (30.0%) were classified as overweight (BMI 23–24.9 kg/m²). Statistical analysis demonstrated a strong relationship between OFD application use and BMI (Contingency Coefficient = 0.631, p = 0.001, Odds Ratio = 0.008, 95% CI: 0.00–0.066). This indicates that higher frequency of OFD application use is associated with a greater likelihood of increased BMI. Conclusion: The study concludes that the use of Online Food Delivery applications has a strong association with Body Mass Index among police officers at Korlantas POLRI in 2025. These findings may serve as a basis for health promotion and educational programs to encourage healthy lifestyle behaviors and prevent obesity and its related health risks within the police force.